Collaborative Governance Actor in the Revitalization Program of Old Banten Religious Tourism Area - Ahmad Sururi (Policy & Governance Review, 2020)
This study discusses the interactions of collaborative governance actors in the revitalization program of the Banten Religious Tourism Area. The purpose of this study is to show the factors that influence the cooperation of local governments as well as analysis of the interaction between local government in the Revitalization Program of the Banten Religious Area. The research method is qualitative descriptive with interview and observation data collection techniques. Data in this study were obtained through primary data and secondary data. The results showed that various factors such as commitment, identification of priority needs, the process of integration and harmonization, participatory and institutional models supported the success of regional cooperation in the revitalization program. The interaction between regional cooperation policy actors in the Revitalization Program of the Old Banten Tourism Area in Serang City at the implementation level has run well, although there are still problems, which include interactions that are indirectly influenced by systems such as politics, economic and social systems. Problems also include the behavior of elites and officials who lean on certain groups.